Recall of Genomic Testing Results Among Patients with Cancer. (26th August 2021) - Wing, Sam E.; Hu, Hengrui; Lopez, Lisa; Solomon, Ilana; Shen, Jenny; Raquel, Catherine; Sur, Melissa; Chao, Joseph; Cristea, Mihaela; Fakih, Marwan; Mortimer, Joanne; Pal, Sumanta; et al.
Abstract : Background: Genomic testing of somatic and germline DNA has transformed cancer care. However, low genetic knowledge among patients may compromise care and health outcomes. Given the rise in genomic testing, we sought to understand patients' knowledge of their genetic test results. Materials and Methods: We conducted a survey-based study with 85 patients at a comprehensive cancer center. We compared self-reported recall of (a) having had somatic/germline testing and (b) their specific somatic/germline results to the genomic test results documented in the medical record. Results: Approximately 30% of patients did not recall having had testing. Of those who recalled having testing, 44% of patients with pathogenic/likely pathogenic germline mutations and 57% of patients with reported somatic alterations did not accurately recall their specific gene or variant-level results. Conclusion: Given significant knowledge gaps in patients' recall of genomic testing, there is a critical need to improve patient-directed education and return-of-results strategies. Abstract : Considering the increase in genomic testing for cancer care, this study aimed to better understand patients' knowledge of their genetic test results.